Innovative systems in the production and organization of forest biomass and urban green areas - P. D’Antonio,; V. N. Scalcione,; C. D’Antonio, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Urban green can be understood in a broad sense, thus indicating a place for leisure and with a filter or interruption function, between the different urban densities.The presence of a proper function of urban green significantly improves the life of those who use the spaces; the aspects are manifold: sanitary, recreational, educational, psycho-social, cultural. In the classification of urban green as furniture green and functional greenforest residues are also included, resulting from the different types of forestry interventions, commonly referred to as forest biomass. For biomass harvesting operations, for energy purposes, they include both silvicultural interventions in forests managed by forest trees and interventions in coppiced forests. This article presents the results of an experiment conducted in an experimental test field, in the province of Treviso, where there is a poplar plant with 4 years of root, and two years of stem. The tests dedicated to the assessment of productivity were conducted in June 2015 by Cnr Ivalsa, in collaboration with Mombracco Energy srl, both partners of the MCV 2.0 project, funded by the Piedmont Region. The production performance of the machine has been analyzed in real working conditions, and in different operating environments, capable of representing the conditions of use typical of the foothills area, and, in particular, squares, poplars and woods, with the aim of obtaining a evaluation of the distribution of working times, productivity, fuel consumption and quality of the wood chips. Laboratory analyzes have made it possible to evaluate the quality of the wood chips and, in particular, the grain size of the same.